HUBUNGAN POLA ASUH ORANG TUA DENGAN PEMBENTUKAN KARAKTER ANAK PADA SISWA KELAS 4 DAN 5 DI SDS IRA MEDAN - Gulo, Lestari; Simatupang, Lenny Lusia (STIKes Murni Teguh, 2025)
Children's character is a collection of traits, habits, and behavioral patterns inherent in a child, which reflect their values, morals, ethics, and personality. Children's character includes how they think, feel, and act in various situations, as well as how they interact with others. This character is formed through a learning process and experience that begins at an early age and is influenced by various factors, including parenting patterns. The purpose of this study was to see the relationship between parenting patterns and the formation of children's character in grades 4 and 5 of SDS IRA Medan. This research method uses a quantitative method with a cross-sectional research design. The population in this study were all students in grades 4 and 5, totaling 67 people. The sampling technique in this study was total sampling. The collected data were analyzed using the Pearson correlation test. The results of this study showed a P-Value of 0.000 or <0.05. It can be concluded that there is a significant relationship between parenting patterns and the formation of children's character in grades 4 and 5 at S DS IRA Medan. It is expected that further researchers will involve larger and more diverse student samples, use experimental research methods, and also add other variable factors that can influence children's character, such as social environment, family economic conditions, media influence, and interactions with peers as considerations to obtain more comprehensive and in-depth results.